PENGUATAN NILAI KARAKTER SERTA PEMBENTUKAN PENDIDIKAN MELALUI PENANAMAN PENCEGAHAN DAN PEMBERANTASAN KORUPSI - Erisa Agus Tiana Umi Saputri (Jurnal Ilmu Hukum Sui Generis, 2023)
Cases of corruption in Indonesia are dynamic, where every year it has increased causing huge financial losses to Indonesia. This corruption activity is certainly detrimental to all aspects of people's lives and will bring disaster to the country's economy caused by uncontrolled acts of corruption. Anti-corruption education is an appropriate control and eradication activity as a comprehensive effort to encourage future generations to develop a firm attitude against all forms of corruption. Prevention or eradication of corruption can be started early by creating anti-corruption values and principles. The way to educate someone's character so that they have anti-corruption properties is by giving them in formal and non-formal education.